ORIENTASI POLITIK MASYARAKAT TERHADAP PEMILIHAN PARTAI POLITIK DI KELURAHAN MELAYU KECAMATANBANJARMASIN TENGAH - Rahman, Gazali (Lambung Mangkurat University Indonesia, 2014)
Gazali Rahman, 2014. Political Orientation Societies against the Selection Political Parties in the Melayu Village District of Banjarmasin Middle. Skripsi. Program Study of Citizenship and Pancasila Education, Department of Sosial Sciences Education, Faculty of Teacher and Education Science, University of Lambung Mangkurat. Counselor(I) Sarbaini, (II) Mariatul Kiptiah. Political real conditions is now happening just to get sheer power and political parties are still not showing good performance, This is evidenced by not channeled aspirations, unfulfilled campaign promises, many corruption and this affects public confidence at the party. This study is intended to know how big the orientation change choice and The highest reason in a choose a political party.This research used the quantitative approach and the sampling technique is simple random sampling. Data was collected by questionnaire technique, interview and documentation.The results showed that the moving party choice 39,56%, remain on the choice 20,33%, golput 3,02%, and not yet decided 37,09%. While supreme reason for the move option because not mercy (do not feel that the perceived), problem of corruption and political program. The highest reason remains that choice is the mercy and good political party program. The highest reason golput namely because dishonesty, not mercy leader and problem of corruption.Based on this study, can be suggested the need for consistency and commitment of a party and party cadres in the fight for the rights of real people. Political parties should also be careful in the selection and recruitment of party cadres in order to have a good quality. moreover, KPU must also continuously socialize election, such as how to choose a good, and the importance of voter participation. Keyword: politics, political orientation, political party